Managing and leading social workers when you are not one yourself : opportunities and challenges in non-government organisations : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Manawatu, New Zealand - Cocker, Suzanne (Massey University, 2019)
Social service management has regularly undergone transformation while adapting to an ever-changing social and political climate. Managerialism and New Public Management has redirected social service management expectations, resulting in the prevalence of employing non-clinical managers. This study uncovered the transferable skills held by managers with qualifications external to social work, and discussed what additional skills are considered required in order to succeed in their role as manager. A qualitative research design was utilised, underpinned by subjective ontology and an interpretivist approach, in order to uncover and highlight the participant voice. Semi-structured interviews gave room for topics to be proposed, and provided participants with the ability to share their experiences. The seven key themes which emerged from this study were management journey, external influences, internal influences, social work knowledge and interest, transferable skills, advice for future managers, and unanticipated findings. The participant group were found to be managers with an eclectic range of experiences, qualifications and knowledge crucial to the survival of social service organisations in the present day. This study uncovered the participant’s steadfast values and unwavering passion, and demonstrated their fierce commitment to empowering their staff, clients and communities.
Keywords: Social work administration; New Zealand; Non-governmental organizations; Management; Executives; 440999 Social work not elsewhere classified